Empowering Businesses: Introducing Digital Marketing Strategies and Human Endeavors - Chusnul Maulidina hidayat; Irawan Randikaparsa; Prasetyo Budi Wicaksana (Universitas Muhammadiyah Purwokerto, 2024)
Addressing the challenges faced by housewives in Pabuaran, Banyumas, this study focuses on the pressing need to empower them with digital marketing knowledge and the integration of Islamic values into their business endeavors. In many rural areas, including Pabuaran, traditional business practices often encounter obstacles in reaching broader markets and adapting to the rapidly evolving digital landscape. Despite being skilled entrepreneurs, housewives may lack access to resources and knowledge regarding effective digital marketing strategies. Additionally, there is a growing recognition of the importance of incorporating ethical and moral principles, such as those derived from Islamic teachings, into business practices. However, there is a gap in understanding how to effectively integrate these principles into modern business operations. Thus, this study aims to bridge these gaps by providing participants with practical knowledge and skills in digital marketing while exploring the application of Islamic values in entrepreneurship. By addressing these challenges, the study seeks to empower housewives in Pabuaran to overcome barriers to market access and enhance the sustainability and ethical integrity of their businesses. Through this empowerment initiative, participants will be equipped to leverage digital marketing tools effectively and align their business practices with Islamic principles, thereby fostering economic growth and social development within their community.